Current Trends in Global Supply Chain Management Investment Policy - L. G Chuvakhina; I. Z Yarygina; V. K Pospelov; O. A Drozdov (International Journal of Supply Chain Management, 2020)
Abstract- To achieve the Sustainable Development Goals of the world economy, significant financial resources and global supply chain are needed. Priority issues are related to the use of investment resources. Almost all sectors of the economy have a real need for investment. Domestic investments is not enough for countries to implement effective structural policies and upgrade fixed assets. They are forced to attract foreign investment. The annual requirements for international investment reach several trillion US dollars. However, foreign investors are in no hurry to expand investments in the economy of foreign countries. Moreover, in 2017-2019 there is a decrease in global direct foreign investment flows. This is largely due to a noticeable reduction in US investment in the economies of the European Union and China as a result of the tightening of the American protectionism policy pursued by the D. Trump administration and the US Federal Reserve to strengthen regulation of foreign companies in the US market. A decrease in the level of international investment under the worsening business climate in the world leads to the increased competition between countries for attracting foreign investment.